Synthesis of Vinyl Sulfones via I2-mediated Alkene Sulfonylations with Thiosulfonates - Hwang, Sang Joon; Shyam, Pranab K.; Jang, Hye Young (Bulletin of the Korean Chemical Society, 2018)
A simple sulfonylation strategy involving I2 and thiosulfonates, as sulfonyl-group precursors, is reported for the synthesis of vinyl sulfones. Sulfonyl radicals are presumed to be generated from thiosulfonates, which subsequently react with styrene or cinnamic acid derivatives to afford a variety of vinyl sulfones under the described reaction conditions. Detailed conditions, the substrate scope, and mechanistic studies are discussed.
Keywords: Cinnamic acid derivatives; Mechanistic studies; Reaction conditions; Sulfonyl groups; Sulfonylation; Thiosulfonate; Vinyl sulfones; Alkene; Iodine; Sulfonylation; Thiosulfonate; Vinyl sulfone